2020
DOI: 10.3390/ijerph17124607
|View full text |Cite
|
Sign up to set email alerts
|

Implant Placement in Patients under Treatment with Rivaroxaban: A Retrospective Clinical Study

Abstract: The management of patients under treatment with Direct Oral Anticoagulants (DOACs) has led clinicians to deal with two clinical issues, such as the hemorrhagic risk in case of non-interruption or the risk of thromboembolism in case of suspension of the treatment. The primary aim of this retrospective study was to evaluate the incidence of perioperative bleeding events and healing complications in patients who were under treatment with Rivaroxaban and who received dental implants and immediate prosthetic restor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 27 publications
(45 reference statements)
0
22
1
Order By: Relevance
“…In the event of placement of a number greater than or equal to four implants, in a recent study in patients receiving rivaroxaban, the DOAC was suspended 24 h before surgery. In this study, only three minor bleeding events treated with compression were observed out of 12 treated patients and 57 placed implants [49].…”
Section: Good Renal Functionmentioning
confidence: 61%
“…In the event of placement of a number greater than or equal to four implants, in a recent study in patients receiving rivaroxaban, the DOAC was suspended 24 h before surgery. In this study, only three minor bleeding events treated with compression were observed out of 12 treated patients and 57 placed implants [49].…”
Section: Good Renal Functionmentioning
confidence: 61%
“…Full texts of 12 articles were obtained for further assessment, resulting in exclusion of a further 4 studies. Finally, 8 studies [6,[11][12][13][14][15][16][17] met eligibility criteria for this review and were included for full analysis (Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…All articles included were observational cohort studies. There were 4 retrospective [6,11,12,17] and 4 prospective [13][14][15][16]; of the prospective studies, 3 [13,14,16] blinded the operator from which patients were taking anticoagulants. A total of 1467 participants were included with a minimum of 2366 implants placed across all studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations